(untitled) (Muitas Vozes, 2023)
Pragmatic studies are interested in demonstrating the concrete use of language in its varied contexts and the effect it has on our listeners on what we say. This work presents an approach related to pragmatics, but specifically to politeness with regard to linguistic behavior, which manages relationships in our society, based on the dialogue records taken from the Tup-154 black box. The research uses as foundation the Theory of Politeness, using the studies of Brown and Levinson (1987) and the concept of the face of Goffman (1967) to demonstrate that the speech act carries a threat to the public image of those included in the chain. command, which can interfere in the decisions of military aircraft pilots, ie, both speaker and listener are prone to be linguistically injured. With the analysis, it was possible to identify a succession of events for the preservation of the face that led to the aircraft accident. Thus, it is possible to conclude that, in hierarchical relationships, among the most uncomfortable types of problems that arise in face negotiation are issues related to loss of status.